Deflection behavior of small diameter steel piles model in FEM analysis for landslide countermeasure - Mujah, Donovan; Rahman, Ekhlasur; Hazarika, Hemanta; Watanabe, Naoto; Ahmad, Fauziah (Curtin University Sarawak, 2013)
This paper aims to elucidate the prevention mechanism of small diameter steel piles (SDSP) and how multirow arrangement of the said piles affects the reinforced slope failure in landslide countermeasure. In this study, finite element method (FEM) analysis employing Mohr-Coulomb’s elastic-perfectly plastic soil model was carried out to simulate the real SDSP piles in which, the effect of the piles’ cross sections (10 mm x 10 mm square and 3 mm in diameter) was considered. The effect of introducing multiple rows arrangement of SDSP in terms of the single, double and triple rows arrangements of those piles were also studied. Based on the results, it was observed that the shearing resistance in different pile cross sections is found to be significantly influenced by the variation of SDSP arrangement. However irrespective of the piles arrangements, failure mode of the ground during landslide is mainly governed by the bending stiffness (EI) of the reinforcing rods.